Forecasting in humanitarian operations: a method for anticipating fast-moving aid supplies - Annisa, Putri Dwi; Kurniawan, Wahyu (Operations Excellence: Journal of Applied Industrial Engineering, 2024)
Given Indonesia's vulnerability to a diverse range of natural and man-made catastrophes, it is crucial to have a well-executed disaster management system in place. The National Disaster Management Agency (BNPB), as the agency responsible for disaster relief in Indonesia, emphasizes the importance of this matter. This study examines the enhancement of disaster logistics, specifically focusing on the difficulties related to the fast movement of humanitarian aid supplies. The main challenge in disaster logistics is the uncertainty of demand following the occurrence of the disaster, together with the possibility of supply disruptions caused by insufficient inventory in warehouses. This research places significant emphasis on expedited delivery of humanitarian aid supplies, which are crucial for prompt relief operations, especially in situations with limited preparation time. The main aim of the study is to create a safety stock level policy for BNPB's national warehouse, which will be determined by analyzing forecasts of demand and lead times. The research findings for the year 2022 indicate a low percentage of errors in demand predictions. This result emphasizes the efficacy of the safety stock strategy in actively dealing with sudden increases in demand and reducing uncertainty associated with supply schedules.